Adaptive area location algorithm combining with packet lost rate and RSSI in wireless sensor networks - LI Fang-min1; HAN Ping1; LUO Ting2 (Tongxin xuebao)
First, the shortcoming of existing location algorithm based on RSSI（received signal strength indication） in WSN（wireless sensor network） was analyzed.Then, supported by plenty of experimental data in different time and space, the distance evaluation model combining with packet lost rate and RSSI which aim at real environment and location algorithm based on this model was provided.It was regarded as a new kind of exploration for research of wireless location.Location experiments were used to evaluate the capability of this algorithm, which proves that WSN nodes running this algorithm can normally work and precision and stability are upper.